2017
DOI: 10.1038/ijo.2017.2
|View full text |Cite|
|
Sign up to set email alerts
|

School environment and policies, child eating behavior and overweight/obesity in urban China: the childhood obesity study in China megacities

Abstract: SEP are heterogeneous in the four Chinese megacities, high-income areas. They affect child unhealthy eating and overweight/obesity, and are critical for fighting childhood obesity in China.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
49
3
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(62 citation statements)
references
References 32 publications
9
49
3
1
Order By: Relevance
“…The ow/ob prevalence in boys was higher and increased faster than in girls, especially in the urban settings. Boys in China have been described as being particularly vulnerable to obesity because of genetic, behavioral, and socio-cultural reasons [10,20]. However, the gender ratios in general and in the urban setting found in our study were on average lower than ratios found by previous studies [8,10].…”
Section: Discussioncontrasting
confidence: 89%
“…The ow/ob prevalence in boys was higher and increased faster than in girls, especially in the urban settings. Boys in China have been described as being particularly vulnerable to obesity because of genetic, behavioral, and socio-cultural reasons [10,20]. However, the gender ratios in general and in the urban setting found in our study were on average lower than ratios found by previous studies [8,10].…”
Section: Discussioncontrasting
confidence: 89%
“…The school built environment was reported to be closely related to PA, but its associations with ov/ob were inconsistent [47][48][49]. Rashad and colleagues identi ed a signi cant and negative association between access to the sports eld at school and BMI [50], while another study reported that BMI was not associated with PA equipment, or vise versa [51,52].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, food offerings in the same type of food outlets may greatly vary by region, except for the case of national chain stores. More work is needed in the future to untangle these complexities, eg, the inclusion of household surveys and individual purchasing and consumption data …”
Section: Discussionmentioning
confidence: 99%